Anguilla anguilla anguilla (Linnaeus 1758 ... - Bariche, Michel; Fricke, Ronald (Zenodo, 2020)
Anguilla anguilla (Linnaeus 1758) —European eel Taxonomy. First record from Lebanon as Anguilla anguilla (Linnaeus 1758) by George et al. (1964: 13); subsequently recorded as Anguilla anguilla (Linnaeus) by Mouneimné (1977: 61); as Anguilla anguilla (Linnaeus 1758) by Mouneimné (2002: 74–75). Recent unpublished records from Tripoli, Nahr Ibrahim, Beirut and Damour (1998–2012). Material in collection: AUBM, FMNH, MNHN, SMF, and USNM. Distribution. Western and eastern Atlantic, Baltic Sea, North Sea, White Sea, Mediterranean Sea, Sea of Marmara, Black Sea: European seas and adjacent watersheds, spawing and larval migration routes to and from the western Atlantic. Introduced in the Caspian Sea basin. Conservation. IUCN: Global (CR: A2bd+4bd, 28 May 2013); Med. (North Africa) (EN: A4 bd, 16 October 2007); CITES Appendix II. Capture and threats: HAB, unknown. Occurrence: Rare. High priority for conservation action. ... : Published as part of Bariche, Michel & Fricke, Ronald, 2020, The marine ichthyofauna of Lebanon: an annotated checklist, history, biogeography, and conservation status, pp. 1-157 in Zootaxa 4775 (1) on page 31, DOI: 10.11646/zootaxa.4775.1.1, http://zenodo.org/record/3983887 ...